HERG quality control and the long QT syndrome. (9th February 2016) - Foo, Brian; Williamson, Brittany; Young, Jason C.; Lukacs, Gergely; Shrier, Alvin
Abstract : hERG cellular processing and quality control. Nascent hERG channels are inserted into the endoplasmic reticulum membrane where they undergo N‐linked glycosylation. Properly folded hERG is exported to the Golgi apparatus where there is additional glycosylation prior to export to the plasma membrane (PM). Nascent hERG channels that fail to fold properly are targeted for Endoplasmic Reticulum Associated Degradation (ERAD). PM resident hERG channels are internalized and either cycled back to the PM or, if misfolded, are targeted for lysosomal degradation. Abstract: Long‐QT syndrome type‐2 (LQT2) is characterized by reduced functional expression of the human ether‐à‐go‐go related (hERG) gene product, resulting in impaired cardiac repolarization and predisposition to fatal arrhythmia. Previous studies have implicated abnormal trafficking of misfolded hERG as the primary mechanism of LQT2, with misfolding being caused by mutations in the hERG gene (inherited) or drug treatment (acquired). More generally, environmental and metabolic stresses present a constant challenge to the folding of proteins, including hERG, and must be countered by robust protein quality control (QC) systems. Disposal of partially unfolded yet functional plasma membrane (PM) proteins by protein QC contributes to the loss‐of‐function phenotype in various conformational diseases including cystic fibrosis (CF) and long‐QT syndrome type‐2 (LQT2). The prevalent view has been that the loss of PM expression of hERG is attributed to biosynthetic block by endoplasmic reticulum (ER) QC pathways. However, there is a growing appreciation for protein QC pathways acting at post‐ER cellular compartments, which may contribute to conformational disease pathogenesis. This article will provide a background on the structure and cellular trafficking of hERG as well as inherited and acquired LQT2. We will review previous work on hERG ER QC and introduce the more novel view that there is a significant peripheral QC at the PM and peripheral cellular compartments. Particular attention is drawn to the unique role of the peripheral QC system in acquired LQT2. Understanding the QC process and players may provide targets for therapeutic intervention in dealing with LQT2.